The Green Treasure of Tipeshwar: A Study on Floristic Biodiversity and Conservation - Ratan D. Dhanorkar (International Journal of Scientific Research in Science and Technology, 2025)
Tipeshwar Wildlife Sanctuary, located in the Yavatmal district of Maharashtra, is a rich biodiversity hotspot known for its diverse flora and fauna. The sanctuary, classified as a Southern Tropical Dry Deciduous Forest, harbors a variety of plant species that play a crucial role in maintaining the ecological balance. This study explores the floristic diversity of Tipeshwar, highlighting key plant species, their ecological significance, and conservation challenges. The research also emphasizes the importance of preserving this natural heritage through sustainable conservation practices.
Keywords: Tipeshwar Wildlife Sanctury; Floristic Biodiversity; Biodiversity Conservation; Forest Ecosystem